Angola to Zydeco Louisiana lives - Fuller, R. Reese; ebrary, Inc. (Jackson : University Press of Mississippi, 2011)
Creative non-fiction pieces originally published in Times of Acadiana and Independent weekly of Lafayette, La.
Includes index.
Electronic reproduction.
Keywords: Interviews -- Louisiana -- Lafayette Region; Interviews -- Louisiana; Lafayette Region (La.) -- Social life and customs -- Anecdotes; Louisiana -- Social life and customs -- Anecdotes; Lafayette Region (La.) -- Biography; Louisiana -- Biography; Electronic books